A battery positive electrode sheet, a preparation method thereof, a solid-state battery, and an electric device
Patent Information
- Application Number
- CN202611139973.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-23
AI Technical Summary
该类氧化性自由基具备极强反应活性,会持续与硫化物固态电解质发生不可逆氧化还原反应,引发电解质链式分解,生成Li2S、多硫化物、低电导惰性产物,造成正极/电解质界面阻抗持续攀升,界面接触劣化,导致电池容量快速衰减、循环稳定性大幅下降
本申请提供一种电池正极片,所述电池正极片包括依次层叠设置的正极集流体、正极活性材料层和陶瓷层,所述陶瓷层中含有陶瓷粉体和自由基猝灭剂。所述陶瓷层中的自由基猝灭剂通过定向捕获氧化性自由基,可以优化正极片与固态电解质膜之间的界面离子传输,实现电池循环稳定性与安全性的协同提升。
Smart Images

Figure CN122968268A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and more specifically, to a battery positive electrode sheet and its preparation method, a solid-state battery, and an electrical device. Background Technology
[0002] Currently, high-nickel ternary layered oxides (such as NCM811) are widely used as positive electrode active materials for sulfide solid-state batteries due to their advantages of high specific capacity and high operating voltage, which can effectively improve the overall energy density of the battery. However, during high-voltage charge-discharge and long-cycle processes, the lattice oxygen in high-nickel cathodes is prone to redox reactions, inducing lattice distortion and oxygen vacancies, and continuously releasing highly oxidizing reactive oxygen species such as superoxide anions and oxygen free radicals. These oxidizing free radicals have extremely high reactivity and will continuously undergo irreversible redox reactions with sulfide solid electrolytes, triggering electrolyte chain decomposition and generating Li2S, polysulfides, and low-conductivity inert products. This causes the cathode / electrolyte interface impedance to continuously increase, interface contact to deteriorate, leading to rapid capacity decay and a significant decrease in cycle stability. At the same time, the continuous interface side reactions induced by free radicals are accompanied by heat accumulation, which can easily induce battery bulging, thermal runaway and other safety problems, seriously restricting the industrial application of sulfide solid-state batteries.
[0003] Current mainstream cathode interface modification methods have significant technical shortcomings, failing to address the root cause of free radical-induced interface failure. Firstly, traditional oxide and phosphate nanocoating processes often employ ALD (Alternating Layer Deposition) and sol-gel methods to construct thin-layer protective structures on the cathode particle surface. These coatings have low ionic conductivity, significantly increasing interfacial impedance. Furthermore, they are susceptible to cracking and detachment during cycling due to electrode volume deformation. After protection failure, interfacial side reactions rebound rapidly, only delaying the side reactions but not halting the free radical chain reaction. Secondly, electrolyte bulk phase doping and electrochemical window modification technologies can only slightly widen the electrolyte's stable voltage range, failing to match the high-voltage operating environment of high-nickel cathodes. They lack the ability to scavenge or quench oxidative free radicals released from the cathode, failing to terminate the chain decomposition reaction. Moreover, doping modification easily leads to a decrease in the bulk electrolyte's ionic conductivity, sacrificing battery rate performance. Third, conventional polymer-ceramic composite buffer layers and in-situ interface phase modification schemes have problems such as poor heat resistance of polymers, easy softening and failure at high temperatures, uncontrollable interface layer thickness, and easy formation of high-resistivity interfaces. They also lack the function of active free radical quenching and cannot fundamentally solve the core problem of continuous degradation of the cathode-electrolyte interface. Summary of the Invention
[0004] The purpose of this application is to overcome the problems existing in the prior art and provide a battery positive electrode sheet and its preparation method, a solid-state battery and an electrical device. The battery positive electrode sheet is provided with a ceramic layer containing ceramic powder and free radical quencher. By directionally capturing oxidative free radicals and optimizing interfacial ion transport, the battery cycle stability and safety are synergistically improved.
[0005] The technical problem solved by this application is achieved by the following technical solution.
[0006] This application provides a battery positive electrode sheet, which includes a positive current collector, a positive active material layer and a ceramic layer stacked sequentially, wherein the ceramic layer contains ceramic powder and a free radical quencher.
[0007] In some embodiments of this application, the proportion of free radical quencher in the ceramic layer is 3wt%-8wt%; Preferably, the free radical quencher includes one or more of trimethylboronic acid ester, tri(fluoromethyl)boronic acid ester, 2,4,6-tri(trifluoromethyl)phenylboronic acid ester, TEMPO, OH-TEMPO, TEMPO-OSO3Li, antioxidant 1010, antioxidant 1076, and N,N'-diphenyl-p-phenylenediamine.
[0008] In some embodiments of this application, the ceramic powder content in the ceramic layer is 60wt%-70wt%; Preferably, the ceramic powder includes one or more of LiAlO2, LiAl5O8, LLZO, Li3BO3, Li2ZrO3, LiNbO3, Al2O3, MgO, and ZrO2.
[0009] In some embodiments of this application, the ceramic layer further contains lithium salt and film-forming aids; Preferably, the lithium salt content in the ceramic layer is 25wt%-30wt%, and the film-forming aid content is 1wt%-3wt%. Preferably, the lithium salt includes one or more of LiFSI, LiTFSI, LiPF6, LiDFOB, LiBOB, and LiBF4, and the film-forming aid includes one or more of PEG, PEO, PPG, PVA, PVP, PVDF, and PVDF-HFP.
[0010] In some embodiments of this application, the ceramic layer comprises the following components by weight percentage: 60wt%-70wt% ceramic powder, 3wt%-8wt% free radical quencher, 25wt%-30wt% lithium salt, and 1wt%-3wt% film-forming aid; Preferably, the thickness of the ceramic layer is 1μm-15μm.
[0011] This application also provides a method for preparing the above-mentioned battery positive electrode sheet, comprising: sequentially coating a positive electrode active material layer and a ceramic layer on the surface of a positive electrode current collector.
[0012] In some embodiments of this application, the method of coating the ceramic layer includes: preparing a slurry from ceramic powder, free radical quencher, lithium salt, and film-forming aid, coating it onto the surface of the positive electrode active material layer, and drying it to obtain a battery positive electrode sheet. Preferably, ceramic powder, free radical quencher, lithium salt, film-forming aid and organic solvent are mixed and ball-milled for 1h-24h to form a uniform slurry, which is then coated on the surface of the positive electrode active material layer and vacuum dried at 80℃-120℃ for 1h-8h to form a ceramic layer with a thickness of 1μm-15μm. Preferably, the organic solvent includes anisole.
[0013] This application also provides a solid-state battery, which includes a positive electrode, a negative electrode, and a solid electrolyte sheet located between the positive electrode and the negative electrode, wherein the positive electrode is the aforementioned positive electrode.
[0014] In some embodiments of this application, the electrolyte in the solid electrolyte sheet includes a sulfide electrolyte.
[0015] This application also provides an electrical device, which includes the solid-state battery described above.
[0016] This application has the following beneficial effects: This application provides a battery positive electrode sheet, comprising a positive electrode current collector, a positive electrode active material layer, and a ceramic layer stacked sequentially. The ceramic layer contains ceramic powder and a free radical quencher. The free radical quencher in the ceramic layer can optimize interfacial ion transport between the positive electrode sheet and the solid electrolyte membrane by directionally capturing oxidative free radicals, thereby achieving a synergistic improvement in battery cycle stability and safety. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 This is a schematic diagram of the structure of the sulfide solid-state battery provided in this application. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0020] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range such as 1, 2, 3, 4, 5, and 6, regardless of the range; in addition, whenever a numerical range is indicated herein, it means including any referenced number (fraction or integer) within the indicated range.
[0021] In this document, terms including "comprising" and the like mean "including but not limited to". "And / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can mean: A alone, A and B simultaneously, or B alone; where A and B can be singular or plural. "At least one" means one or more, and "more than one" means two or more. "At least one", "at least one of the following", or similar expressions refer to any combination of these items, including any combination of singular or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in this application are commercially available or can be prepared using existing methods.
[0022] The following is a detailed description of a battery positive electrode sheet, its preparation method, a solid-state battery, and an electrical device provided in the embodiments of this application.
[0023] In a first aspect, this application provides a battery positive electrode sheet, the battery positive electrode sheet comprising a positive electrode current collector, a positive electrode active material layer and a ceramic layer stacked sequentially, wherein the ceramic layer contains ceramic powder and a free radical quencher.
[0024] Current sulfide solid-state batteries have high ionic conductivity (10) -3 -10 -2 S / cm and good interface compatibility have become the core directions for next-generation energy storage devices, and their positive electrode plates generally adopt ternary layered oxides (LiNi). x Co y Mn z O2, NCM) are used as active materials, combined with binders (such as SBR, HNBR, etc.) and sulfide electrolytes (such as LiPSCl, Li 10 GeP2S 12 It is prepared by combining high-nickel ternary materials (such as NCM811) with conductive agents (such as VGCF). To improve battery energy density, the application of high-nickel ternary materials (such as NCM811) is becoming increasingly widespread. However, during high-voltage charging, oxygen anions easily participate in redox reactions through transition metal-oxygen (TM-O) covalent bonds, forming oxygen holes and releasing oxidizing free radicals (such as O-•, O2). - ).
[0025] (1) Oxidizing free radicals readily undergo redox reactions with sulfide electrolytes, leading to electrolyte decomposition and the generation of Li2S and P2S. x Low ionic conductivity products significantly increase interfacial impedance by 30%-50%, leading to a decrease in battery cycle life. (2) The interfacial oxidation reaction initiated by oxidative free radicals is accompanied by heat release, which can easily trigger thermal runaway under high voltage and high temperature conditions, seriously affecting the battery safety performance; (3) Existing interface optimization schemes (such as electrolyte bulk phase doping, LiNbO3 coating) can only suppress chemical side reactions or space charge layer effects, but cannot directionally capture and eliminate oxidative free radicals, thus providing limited improvement in interface stability. Existing solid-state battery cathode interface modification technologies generally suffer from technical bottlenecks such as the inability to directionally remove oxidative free radicals, difficulty in blocking chain side reactions, and difficulty in synergistically balancing interface impedance and safety, making it difficult to simultaneously meet the industrialization requirements of high energy density, long cycle life, and high safety performance. This application proposes a lithium-ion battery cathode sheet with a free radical quenching functional ceramic layer. By constructing a composite ceramic interface layer with physical protection, ion conduction, and free radical quenching functions on the surface of the cathode active material layer, it directionally captures and quenches oxidative free radicals generated during high-voltage cycling, blocks the chain oxidation decomposition reaction of the electrolyte, and optimizes the interface ion transport capability, thereby achieving a synergistic improvement in the cycle stability and safety performance of solid-state batteries and solving the aforementioned problems of existing technologies.
[0026] In some alternative embodiments, the proportion of the free radical quencher in the ceramic layer is 3wt%-8wt%. For example, the amount of free radical quencher in the ceramic layer can be 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, and other values between 3wt% and 8wt%. Preferably, the free radical quencher includes one or more of trimethylboronic acid ester, tri(fluoromethyl)boronic acid ester, 2,4,6-tri(trifluoromethyl)phenylboronic acid ester, TEMPO, OH-TEMPO, TEMPO-OSO3Li, antioxidant 1010, antioxidant 1076, and N,N'-diphenyl-p-phenylenediamine.
[0027] This application provides a battery positive electrode sheet in which a free radical quencher introduced into the ceramic layer can play the following roles: (1) Free radical capture: The free radical quencher in the ceramic layer captures oxidative free radicals (such as O2) released from the positive electrode through empty orbital coordination or electron transfer. - O2 - (1) Forming stable chemical products and blocking the chain reaction of "free radical-electrolyte oxidation"; (2) Optimizing ion transport: The introduction of lithium salt improves the ion conductivity of the ceramic layer, and with the mechanical support of the ceramic matrix, maintains close contact at the interface and reduces ion transport impedance; (3) Physical isolation protection: The electronic insulation properties of the ceramic layer can inhibit the migration of transition metal ions, and at the same time block the direct contact between the positive electrode and the electrolyte, reducing the occurrence of chemical side reactions.
[0028] In some optional embodiments, the proportion of ceramic powder in the ceramic layer is 60wt%-70wt%. For example, the amount of ceramic powder in the ceramic layer can be 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt%, 70wt%, and other values between 60wt% and 70wt%. Preferably, the ceramic powder includes one or more of LiAlO2, LiAl5O8, LLZO, Li3BO3, Li2ZrO3, LiNbO3, Al2O3, MgO, and ZrO2.
[0029] The positive electrode sheet provided in this application uses a ceramic layer on the surface of the positive electrode active material layer, comprising both lithium oxide and lithium-free materials. The selected lithium oxide material has a wide electrochemical window and excellent chemical inertness, serving as a buffer layer to prevent the diffusion of transition metal ions into the solid electrolyte, avoiding the formation of a passivation high-resistance layer and maintaining stable interface contact during long-term cycling. Furthermore, the lithium oxide does not decompose or release oxygen at high temperatures, isolating the high-voltage positive electrode from oxygen release and reducing severe exothermic side reactions. Additionally, ternary and lithium-rich manganese-based positive electrodes exhibit lattice volume expansion and contraction during lithium insertion and extraction, which can easily lead to separation between the positive electrode and the solid electrolyte during repeated cycling, creating voids that block ion pathways. The rigid ceramic framework of the lithium oxide material can constrain lattice distortion of the positive electrode particles and possesses lithium conductivity, maintaining a continuous lithium-ion transport network even with minor interface deformation, mitigating interface failure. The aforementioned lithium oxide material is electrochemically stable over a wide voltage range, does not decompose, and is suitable for high-energy-density solid-state battery systems. Ceramic materials without lithium oxides, such as Al2O3, MgO, and ZrO2, have specific advantages such as low cost, readily available raw materials, good chemical corrosion resistance, excellent thermal stability, and high mechanical hardness. Adding one or more of these lithium oxide-containing and lithium oxide-free materials to the ceramic layer can suppress interfacial side reactions between the positive electrode active material and the sulfide solid electrolyte, reduce interfacial impedance, and buffer volume stress, which is beneficial for improving the cycle life, rate performance, and energy density of solid-state batteries.
[0030] In some alternative embodiments, the ceramic layer also contains a lithium salt; Preferably, the lithium salt content in the ceramic layer is 25wt%-30wt%. For example, the amount of lithium salt in the ceramic layer can be 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, or other values between 25wt% and 30wt%. Preferably, the lithium salt comprises one or more of LiFSI, LiTFSI, LiPF6, LiDFOB, LiBOB, and LiBF4. The introduction of the lithium salt increases the ionic conductivity of the ceramic interlayer, and, in conjunction with the mechanical support of the ceramic matrix, maintains tight interfacial contact and reduces ion transport impedance.
[0031] In some alternative embodiments, the ceramic layer further contains a film-forming aid; Preferably, the proportion of film-forming aid is 1wt%-3wt%. For example, the amount of film-forming aid in the ceramic layer can be 1wt%, 2wt%, 3wt%, or other values between 1wt% and 3wt%. Preferably, the film-forming aid includes one or more of PEG, PEO, PPG, PVA, PVP, PVDF, and PVDF-HFP. The introduction of the film-forming aid can enhance the adhesion between the coating and the current collector and optimize the slurry processing performance. Furthermore, it can actively construct a stable artificial interface layer (CEI / SEI), effectively suppressing side reactions, thereby significantly improving the cycle stability and safety of the battery under high voltage and high load conditions.
[0032] In some alternative embodiments, the ceramic layer comprises the following components by weight percentage: 60wt%-70wt% ceramic powder, 3wt%-8wt% free radical quencher, 25wt%-30wt% lithium salt, and 1wt%-3wt% film-forming aid. For example, the amount of ceramic powder in the ceramic layer can be 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt%, 70wt%, and other values between 60wt% and 70wt%, the amount of free radical quencher can be 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, and other values between 3wt% and 8wt%, the amount of lithium salt can be 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, and other values between 25wt% and 30wt%, and the amount of film-forming aid can be 1wt%, 2wt%, 3wt%, and other values between 1wt% and 3wt%. Preferably, the thickness of the ceramic layer is 1μm-15μm.
[0033] Secondly, this application also provides a method for preparing the above-mentioned battery positive electrode sheet, comprising: sequentially coating a positive electrode active material layer and a ceramic layer on the surface of a positive electrode current collector.
[0034] In some optional embodiments, the method of coating the ceramic layer includes: preparing a slurry from ceramic powder, free radical quencher, lithium salt, and film-forming aid, coating it onto the surface of the positive electrode active material layer, and drying it to obtain a battery positive electrode sheet; Preferably, ceramic powder, free radical quencher, lithium salt, film-forming aid and organic solvent are mixed and ball-milled for 1h-24h to form a uniform slurry, which is then coated on the surface of the positive electrode active material layer and vacuum dried at 80℃-120℃ for 1h-8h to form a ceramic layer with a thickness of 1μm-15μm. Preferably, the organic solvent includes anisole. Exemplarily, the ball milling time can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, or other values between 1h and 24h, and the vacuum drying temperature can be 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, or 11℃. Other values between 0℃, 115℃, and 120℃; time can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, or other values between 1h and 8h; ceramic layer thickness can be 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, or other values between 1μm and 15μm.
[0035] As can be seen from the above, this application provides a battery positive electrode sheet, which includes a positive electrode current collector, a positive electrode active material layer, and a ceramic layer stacked sequentially. The ceramic layer contains ceramic powder, a free radical quencher, lithium salt, and a film-forming aid. The ceramic powder is selected from ceramic materials with a wide electrochemical window, high voltage stability, electronic insulation, compatibility with ternary cathode / sulfide electrolytes, and wet-coating capability. The ceramic powder in the ceramic layer simultaneously performs functions such as physical barrier, lithium-ion conduction, suppression of lattice oxygen evolution, and mechanical support. The free radical quencher in the ceramic layer achieves broad-spectrum scavenging of O2 by capturing oxygen free radicals through empty orbital coordination and electron transfer to disproportionate superoxide species. - O2 - Lithium salts enhance the bulk ionic conductivity of the ceramic layer, promote the formation of a stable CEI film, and improve solid-solid interface contact. The lithium salts selected in this application are characterized by high-pressure stability, easy dissociation of anions, compatibility with ceramic materials and free radical quenchers, and the ability to inhibit sulfide decomposition. Film-forming aids help to form a continuous, dense, and high-performance coating.
[0036] Thirdly, this application also provides a solid-state battery, which includes a positive electrode, a negative electrode, and a solid electrolyte sheet located between the positive electrode and the negative electrode, wherein the positive electrode is the same as described in the first or second aspect.
[0037] In some alternative embodiments, the positive electrode active material layer in the battery positive electrode sheet may be disposed on one or both surfaces of the positive electrode current collector.
[0038] Those skilled in the art can choose a suitable method to prepare the battery positive electrode sheet. For example, it may include the following steps: mixing positive electrode active material, binder and conductive agent to form a slurry, and then coating it onto the positive electrode current collector.
[0039] The specific type of positive electrode active material is not particularly limited, as long as it can satisfy the requirements for lithium ion insertion and extraction. The positive electrode active material can be a layered structure material, allowing lithium ions to diffuse in two-dimensional space, or a spinel structure, allowing lithium ions to diffuse in three-dimensional space. Preferably, the positive electrode active material can be selected from one or more of lithium transition metal oxides, or compounds obtained by adding other transition metals, non-transition metals, or non-metals to lithium transition metal oxides. Specifically, the positive electrode active material is preferably selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.
[0040] In the positive electrode sheet of the battery, the positive electrode active material layer may further include a conductive agent and a binder. The type and content of the conductive agent and binder are not specifically limited and can be selected according to actual needs. The binder typically includes styrene-based block copolymer binders. Compared to the SEBS binder, organic solvents are generally good solvents; that is, the styrene-based block copolymer binder typically has good solubility in organic solvents. For example, the fluorinated polyolefin binder may include, but is not limited to, SEBS, SEBS, or their modified derivatives, mainly including SBS, SIS, and SEPS. The mass percentage content of the binder in the positive electrode material layer may be limited because the binder itself has poor conductivity, therefore the amount of binder used cannot be too high. The conductive agent of the battery positive electrode sheet can be various conductive agents suitable for secondary batteries in the art, for example, it may be one or more of the following, including but not limited to superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0041] In the positive electrode of a battery, the type of positive current collector is not specifically limited and can be selected according to actual needs. The positive current collector is typically a layer, and is generally a structure or component capable of collecting current. The positive current collector can be any material suitable for use as a positive current collector in electrochemical energy storage devices. For example, the positive current collector can be, but is not limited to, metal foil, and more specifically, can be, but is not limited to, nickel foil and aluminum foil.
[0042] In some alternative embodiments, the battery negative electrode typically includes a negative current collector and a negative active material layer located on the surface of the negative current collector, the negative active material layer typically comprising a negative active material.
[0043] Those skilled in the art can choose a suitable method to prepare the battery negative electrode sheet. For example, it may include the following steps: mixing negative electrode active material, binder and conductive agent to form a slurry, and then coating it onto the negative electrode current collector.
[0044] The negative electrode active material can be any material suitable for lithium-ion secondary batteries, including but not limited to artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material can be selected from one or more of elemental silicon, silicon-oxygen compounds, silicon-carbon compounds, silicon-nitrogen compounds, and silicon alloys. The tin-based material can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as battery negative electrode active materials can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0045] The negative electrode current collector is typically a structure or component that collects current. It can be any material suitable for use as a negative electrode current collector in a lithium secondary battery. For example, it can be, but is not limited to, metal foil, and more specifically, copper foil. Furthermore, the battery negative electrode sheet can also be a lithium sheet.
[0046] In some optional embodiments, the solid electrolyte located between the positive and negative electrodes is a sulfide-based solid electrolyte. As an example, the sulfide-based solid electrolyte may include one or more of the following: argyrocerium sulfide type, LGPS type, Li₂S-GeS₂ type, Li₂S-P₂S₅ type, Li₂S-SiS₂ type, and Li₂S-MS-P₂S₅ type sulfide solid electrolyte materials. M may include one or more of Si, Ge, Sn, and Al. Specifically, the argyrocerium sulfide type solid electrolyte material may include materials with the chemical formula Li… 6±s P 1-j A j S 5±s-t B t X 1±s The material has the following properties: 0≤j<1, 0≤t<1, 0≤s<1. A includes one or more elements selected from Ge, Si, Sn, and Sb; B includes one or more elements selected from O, Se, and Te; and X includes one or more elements selected from Cl, Br, I, and F. LGPS-type sulfide solid electrolyte materials may include those with the chemical formula Li. 10±δ5 Ge 1-g G g P 2-q Q q S 12-w W wThe material has the following properties: 0 ≤ δ5 < 1, 0 ≤ g ≤ 1, 0 ≤ q ≤ 2, 0 ≤ w < 1, G includes one or two elements selected from Si and Sn, Q includes Sb, and W includes one or more elements selected from O, Se, Te, Cl, Br, I, and F. As an example, sulfide solid electrolyte materials may include Li6PS5Cl, Li6PS5Br, Li... 10 GeP2S 12 Li3PS4, Li7P3S 11 One or more of the following. The solid electrolyte sheet acts as a conductor of ions between the positive and negative electrodes. Based on the synergistic effect of organic polymers and lithium salts in this application, the volume expansion of porous silicon-carbon materials is mitigated, interfacial contact is improved, and the SEI film is stabilized, making the silicon-carbon composite negative electrode material provided in this application more suitable for solid-state batteries, especially all-solid-state batteries composed of sulfide-based solid electrolytes.
[0047] In some optional embodiments, the solid electrolyte sheet may or may not include a binder, depending on the manufacturing process of the solid-state battery cell. As an example, the binder typically includes styrene-based block copolymer binders. Organic solvents are generally good solvents relative to the SEBS binder; that is, the styrene-based block copolymer binder typically has good solubility in organic solvents. For example, the fluorinated polyolefin binder may include, but is not limited to, SEBS, SEBS, or their modified derivatives, mainly including SBS, SIS, and SEPS. In addition, the binder may include one or more of the following: styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, methyl vinyl silicone rubber, nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, cis-butadiene rubber (BR), ethyl cellulose, fluororubber, and acrylate rubber.
[0048] In some implementations, see Figure 1 The solid-state battery provided in this application includes: a positive electrode sheet, a negative electrode sheet, and a solid electrolyte sheet disposed between the negative electrode sheet and the positive electrode sheet. The positive electrode sheet includes an aluminum foil, a positive electrode coating coated on the surface of the aluminum foil, and a ceramic layer coated on the surface of the positive electrode coating. The negative electrode sheet includes a copper foil and a negative electrode coating coated on the surface of the copper foil. During the charging and discharging process of the battery, active ions (e.g., lithium ions) repeatedly insert and extract between the positive and negative electrode sheets. The electrolyte sheet, located between the positive and negative electrode sheets, mainly serves to conduct active ions.
[0049] In some embodiments, the solid-state battery provided in this application includes an outer packaging. This outer packaging can be used to encapsulate the aforementioned electrode assembly and solid electrolyte sheet.
[0050] In some embodiments, the solid-state battery provided in this application includes a rigid outer casing, such as a hard plastic casing, an aluminum casing, or a steel casing. The outer casing of the secondary battery can also be a soft-pack, such as a pouch-type soft-pack. The soft-pack material can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0051] This application does not impose any particular restrictions on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape.
[0052] In some implementations, the battery positive electrode, battery negative electrode, and solid electrolyte membrane can be fabricated into a battery cell using a winding process or a stacking process.
[0053] In some alternative embodiments, the aforementioned battery cells can be assembled into a battery module, and the number of battery cells contained in the battery module can be multiple, the specific number of which can be adjusted according to the application and capacity of the battery module.
[0054] In some alternative embodiments, the battery modules described above can be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0055] Fourthly, this application also provides an electrical device, which includes the aforementioned solid-state battery.
[0056] The electrical device provided in this application may include the aforementioned battery cells, battery modules, or battery packs. The aforementioned battery cells, battery modules, or battery packs can be used as the power source for the electrical device or as the energy storage unit for the electrical device. The electrical device may be, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0057] The electrical device can be configured to use individual battery cells, battery modules, or battery packs according to its usage requirements.
[0058] In specific implementations, the electrical device can be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of the lithium-ion battery for this electrical device, a battery pack or battery module can be used. Another example of an electrical device could be a mobile phone, tablet computer, laptop computer, etc.
[0059] Those skilled in the art will understand that the various limitations or optional ranges for the selection of components, component content and physicochemical properties of materials in the different embodiments of this application mentioned above can be arbitrarily combined, and the various embodiments obtained by such combinations are still within the scope of this application and are considered as part of the disclosure of this specification.
[0060] Unless otherwise specified, the various parameters mentioned in this specification have general meanings known in the art and can be measured using methods known in the art. For example, they can be tested according to the methods given in the embodiments of this application. In addition, the optional ranges and options of various parameters given in the various optional embodiments can be combined arbitrarily, and all such combinations are considered to be within the scope of disclosure of this application.
[0061] The embodiments of this application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. In addition, unless otherwise specified, all reagents used in the following embodiments are commercially available or can be synthesized according to the methods described herein or known methods. For reaction conditions not listed, they are also readily available to those skilled in the art.
[0062] This application provides a method for preparing a battery positive electrode sheet, including the following steps: Step 1: Coat the surface of the positive electrode current collector with a layer of positive electrode active material: Mix NCM811 (50-90wt.%), PVDF (1-10wt.%), LiPSCl electrolyte (1-30wt.%), and carbon nanotubes (1-10wt.%), add anisole to make a slurry, coat it on the surface of the current collector (such as aluminum foil), and vacuum dry at 80-120℃ for 2-12h. After compaction, the density is 5-15mg / cm². Step 2: Coating a ceramic layer onto the surface of the positive electrode active material layer: Ceramic powder, free radical quencher, lithium salt, film-forming aid, and organic solvent are mixed and ball-milled for 1-24 hours to form a uniform slurry. This slurry is then coated onto the surface of the positive electrode active material layer and vacuum-dried at 80℃-120℃ for 1-8 hours to form a ceramic layer with a thickness of 1μm-15μm. The ceramic layer comprises the following components by mass percentage: 60wt%-70wt% ceramic powder, 3wt%-8wt% free radical quencher, 25wt%-30wt% lithium salt, and 1wt%-3wt% film-forming aid. The ceramic powder includes one or more of LiAlO2, LiAl5O8, LLZO, Li3BO3, Li2ZrO3, LiNbO3, Al2O3, MgO, and ZrO2. The free radical quenchers include one or more of trimethylboronic acid ester, tris(fluoromethyl)boronic acid ester, 2,4,6-tris(trifluoromethyl)phenylboronic acid ester, TEMPO, OH-TEMPO, TEMPO-OSO3Li, antioxidant 1010, antioxidant 1076, and N,N'-diphenyl-p-phenylenediamine. The lithium salts include one or more of LiFSI, LiTFSI, LiPF6, LiDFOB, LiBOB, and LiBF4. The film-forming aids include one or more of PEG, PEO, PPG, PVA, PVP, PVDF, and PVDF-HFP.
[0063] Example 1 Step 1: Coating the surface of the positive electrode current collector with a positive electrode active material layer: Mix NCM811 (70wt.%), PVDF (3wt.%), LiPSCl electrolyte (20wt.%), and carbon nanotubes (7wt.%), add anisole to make a slurry, coat it onto the aluminum foil current collector, vacuum dry at 120℃ for 12h, and compact it to a density of 15mg / cm². Step 2: Coating a ceramic layer on the surface of the positive electrode active material layer: Disperse LiAlO2 (65wt.%), TTFEB (5wt.%), LiFSI (28wt.%), and PEG (2wt.%) in anisole, ball mill for 24 h to form a uniform slurry, coat it on the surface of the positive electrode active material layer, and vacuum dry it at 80℃ for 8 h to form a ceramic layer with a thickness of 15 μm; Step 3, Battery Assembly: The above positive electrode, LiPSCl electrolyte layer (80μm), silicon-carbon negative electrode, and copper foil current collector are laminated sequentially and packaged into a soft-pack battery in an argon glove box (dew point ≤ -40℃). Example 2 Step 1: Coating the surface of the positive electrode current collector with a positive electrode active material layer: Mix NCM622 (70wt.%), SEBS (3wt.%), LiPSCl electrolyte (20wt.%), and carbon nanotubes (7wt.%), add anisole to make a slurry, coat it onto the aluminum foil current collector, vacuum dry at 120℃ for 12h, and compact it to a density of 15mg / cm². Step 2: Coating a ceramic layer on the surface of the positive electrode active material layer: Disperse LiNbO3 (60wt.%), TEMPO (8wt.%), LiTFSI (30wt.%), and PVP (2wt.%) in anisole, ball mill for 24 h to form a uniform slurry, coat it on the surface of the positive electrode active material layer, and vacuum dry at 80℃ for 8 h to form a ceramic layer with a thickness of 8 μm; Step 3, Battery Assembly: The above positive electrode, LiPSCl electrolyte layer (80μm), silicon-carbon negative electrode, and copper foil current collector are laminated sequentially and packaged into a soft-pack battery in an argon glove box (dew point ≤ -40℃).
[0064] Example 3 Step 1: Coating the surface of the positive electrode current collector with a positive electrode active material layer: Mix NCM811 (70wt.%), SEBS (3wt.%), LiPSCl electrolyte (20wt.%), and carbon nanotubes (7wt.%), add anisole to make a slurry, coat it onto the aluminum foil current collector, vacuum dry at 120℃ for 12h, and compact it to a density of 15mg / cm². Step 2: Coating a ceramic layer on the surface of the positive electrode active material layer: Disperse LLZO (70wt.%), OH-TEMPO (3wt.%), LiDFOB (28wt.%), and PVDF-HFP (1wt.%) in anisole, ball mill for 18h to form a uniform slurry, coat it on the surface of the positive electrode active material layer, and vacuum dry at 80℃ for 8h to form a ceramic layer with a thickness of 10μm; Step 3, Battery Assembly: The above positive electrode, LiPSCl electrolyte layer (80μm), silicon-carbon negative electrode, and copper foil current collector are laminated sequentially and packaged into a soft-pack battery in an argon glove box (dew point ≤ -40℃). Example 4 Step 1: Coating the surface of the positive electrode current collector with a positive electrode active material layer: Mix NCM811 (70wt.%), SEBS (3wt.%), LiPSCl electrolyte (20wt.%), and carbon nanotubes (7wt.%), add anisole to make a slurry, coat it onto the aluminum foil current collector, vacuum dry at 120℃ for 12h, and compact it to a density of 15mg / cm². Step 2: Coating a ceramic layer on the surface of the positive electrode active material layer: Disperse Li2ZrO3 (62wt.%), antioxidant 1010 (6wt.%), LiBOB (28wt.%), and PEG (3wt.%) in anisole, ball mill for 8 hours to form a uniform slurry, coat it on the surface of the positive electrode active material layer, and vacuum dry it at 80℃ for 8 hours to form a ceramic layer with a thickness of 5μm; Step 3, Battery Assembly: The above positive electrode, LiPSCl electrolyte layer (80μm), silicon-carbon negative electrode, and copper foil current collector are laminated sequentially and packaged into a soft-pack battery in an argon glove box (dew point ≤ -40℃).
[0065] Example 5 Step 1: Coating the surface of the positive electrode current collector with a positive electrode active material layer: Mix NCM811 (70wt.%), PVDF (3wt.%), LiPSCl electrolyte (20wt.%), and carbon nanotubes (7wt.%), add anisole to make a slurry, coat it onto the aluminum foil current collector, vacuum dry at 120℃ for 12h, and compact it to a density of 15mg / cm². Step 2: Coating a ceramic layer on the surface of the positive electrode active material layer: Al2O3+ZrO2 (mass ratio 1:1) (65wt.%), 2,4,6-tris(trifluoromethyl)phenylboronic acid ester (4wt.%), LiPF6+LiFSI (mass ratio 1:1) 27wt.%, and PVA (1wt.%) are dispersed in anisole, ball-milled for 20h to form a uniform slurry, coated on the surface of the positive electrode active material layer, and vacuum dried at 95℃ for 7h to form a ceramic layer with a thickness of 12μm; Step 3, Battery Assembly: The above positive electrode, LiPSCl electrolyte layer (80μm), silicon-carbon negative electrode, and copper foil current collector are laminated sequentially and packaged into a soft-pack battery in an argon glove box (dew point ≤ -40℃). Example 6 Step 1: Coating the surface of the current collector with a positive electrode active material layer: Mix NCM811 (70wt.%), PVDF (3wt.%), LiPSCl electrolyte (20wt.%), and carbon nanotubes (7wt.%), add anisole to make a slurry, coat it onto the aluminum foil current collector, vacuum dry at 120℃ for 12h, and compact it to a density of 15mg / cm². Step 2: Coating a ceramic layer on the surface of the positive electrode active material layer: Disperse Li2ZrO3 (65wt.%), N,N'-diphenyl-p-phenylenediamine (3wt.%), LiDFOB (26wt.%), and PPG (2wt.%) in anisole, ball mill for 18 hours to form a uniform slurry, coat it on the surface of the positive electrode active material layer, and vacuum dry at 110℃ for 8 hours to form a ceramic layer with a thickness of 10μm; Step 3, Battery Assembly: The above positive electrode, LiPSCl electrolyte layer (80μm), silicon-carbon negative electrode, and copper foil current collector are laminated sequentially and packaged into a soft-pack battery in an argon glove box (dew point ≤ -40℃).
[0066] Example 7 Step 1: Coating the surface of the current collector with a positive electrode active material layer: Mix NCM811 (70wt.%), SEBS (3wt.%), LiPSCl electrolyte (20wt.%), and carbon nanotubes (7wt.%), add anisole to make a slurry, coat it onto the aluminum foil current collector, vacuum dry at 120℃ for 12h, and compact it to a density of 15mg / cm². Step 2: Coating a ceramic layer on the surface of the positive electrode active material layer: Disperse Li2ZrO3 (62wt.%), antioxidant 1010 (6wt.%), LiBOB (28wt.%), and PEG (3wt.%) in anisole, ball mill for 8 hours to form a uniform slurry, coat it on the surface of the positive electrode active material layer, and vacuum dry at 80℃ for 8 hours to form a ceramic layer with a thickness of 5μm; Step 3, Battery Assembly: The above positive electrode, LiPSCl electrolyte layer (80μm), silicon-carbon negative electrode, and copper foil current collector are laminated sequentially and packaged into a soft-pack battery in an argon glove box (dew point ≤ -40℃).
[0067] Example 8 Step 1: Coating the surface of the current collector with a positive electrode active material layer: Mix NCM811 (70wt.%), PVDF (3wt.%), LiPSCl electrolyte (20wt.%), and carbon nanotubes (7wt.%), add anisole to make a slurry, coat it onto the aluminum foil current collector, vacuum dry at 120℃ for 12h, and compact it to a density of 15mg / cm². Step 2: Coating a ceramic layer on the surface of the positive electrode active material layer: Al2O3+ZrO2 (mass ratio 1:1) (65wt.%), 2,4,6-tris(trifluoromethyl)phenylboronic acid ester (4wt.%), LiPF6+LiFSI (mass ratio 1:1) 27wt.%, and PVA (1wt.%) are dispersed in anisole, ball-milled for 20h to form a uniform slurry, coated on the surface of the positive electrode active material layer, and vacuum dried at 95℃ for 7h to form a ceramic layer with a thickness of 12μm; Step 3, Battery Assembly: The above positive electrode, LiPSCl electrolyte layer (80μm), silicon-carbon negative electrode, and copper foil current collector are laminated sequentially and packaged into a soft-pack battery in an argon glove box (dew point ≤ -40℃).
[0068] Comparative Example 1 Step 1: Coating the surface of the current collector with a positive electrode active material layer: Mix NCM811 (70wt.%), PVDF (3wt.%), LiPSCl electrolyte (20wt.%), and carbon nanotubes (7wt.%), add anisole to make a slurry, coat it onto the aluminum foil current collector, vacuum dry at 120℃ for 12h, and compact it to a density of 15mg / cm². Step 2, Battery Assembly: The above positive electrode, LiPSCl electrolyte layer (80μm), silicon-carbon negative electrode, and copper foil current collector are laminated sequentially and packaged into a soft-pack battery in an argon glove box (dew point ≤ -40℃). Comparative Example 2 Step 1: Coating the surface of the current collector with a positive electrode active material layer: Mix NCM811 (70wt.%), PVDF (3wt.%), LiPSCl electrolyte (20wt.%), and carbon nanotubes (7wt.%), add anisole to make a slurry, coat it onto the aluminum foil current collector, vacuum dry at 120℃ for 12h, and compact it to a density of 15mg / cm². Step 2: Coating a ceramic layer on the surface of the positive electrode active material layer: Disperse LiAlO2 (65wt.%), LiFSI (28wt.%), and PEG (2wt.%) in anisole, ball mill for 24h to form a uniform slurry, coat it on the surface of the positive electrode active material layer, and vacuum dry at 80℃ for 8h to form a ceramic layer with a thickness of 15μm. Step 3, Battery Assembly: The above positive electrode, LiPSCl electrolyte layer (80μm), silicon-carbon negative electrode, and copper foil current collector are laminated sequentially and packaged into a soft-pack battery in an argon glove box (dew point ≤ -40℃). Comparative Example 3 Step 1: Coating the surface of the current collector with a positive electrode active material layer: Mix NCM811 (70wt.%), PVDF (3wt.%), LiPSCl electrolyte (20wt.%), and carbon nanotubes (7wt.%), add anisole to make a slurry, coat it onto the aluminum foil current collector, vacuum dry at 120℃ for 12h, and compact it to a density of 15mg / cm². Step 2: Coating a ceramic layer on the surface of the positive electrode active material layer: Disperse LiAlO2 (68wt.%), TTFEB (2wt.%), LiFSI (28wt.%), and PEG (2wt.%) in anisole, ball mill for 24 h to form a uniform slurry, coat it on the surface of the positive electrode active material layer, and vacuum dry at 80℃ for 8 h to form a ceramic layer with a thickness of 15 μm; Step 3, Battery Assembly: The above positive electrode, LiPSCl electrolyte layer (80μm), silicon-carbon negative electrode, and copper foil current collector are laminated sequentially and packaged into a soft-pack battery in an argon glove box (dew point ≤ -40℃). Comparative Example 4 Step 1: Coating the surface of the current collector with a positive electrode active material layer: Mix NCM811 (70wt.%), PVDF (3wt.%), LiPSCl electrolyte (20wt.%), and carbon nanotubes (7wt.%), add anisole to make a slurry, coat it onto the aluminum foil current collector, vacuum dry at 120℃ for 12h, and compact it to a density of 15mg / cm². Step 2: Coating a ceramic layer on the surface of the positive electrode active material layer: Disperse LiAlO2 (65wt.%), TTFEB (10wt.%), LiFSI (28wt.%), and PEG (2wt.%) in anhydrous ethanol, ball mill for 24 h to form a uniform slurry, coat it on the surface of the positive electrode active material layer, and vacuum dry at 80℃ for 8 h to form a ceramic layer with a thickness of 15 μm; Step 3, Battery Assembly: The above positive electrode, LiPSCl electrolyte layer (80μm), silicon-carbon negative electrode, and copper foil current collector are laminated sequentially and packaged into a soft-pack battery in an argon glove box (dew point ≤ -40℃).
[0069] Performance testing: 1. Capacity retention test: 1) Place the assembled soft-pack solid-state battery in a 25°C constant temperature chamber for 12 hours to allow the internal interface to be fully wetted and stabilized.
[0070] 2) The test is conducted using the Landon / Newway battery testing system in an argon atmosphere or an explosion-proof chamber.
[0071] 3) Activation procedure: Charge to 4.3V with a constant current of 0.1C, switch to constant voltage to current of 0.02C; then discharge to 2.8V with a constant current of 0.1C, cycle 3 times, and record the discharge capacity of the third cycle as the initial discharge capacity.
[0072] 4) Long-cycle regime: Charge to 4.3V with constant current at 0.3C, cut off with constant voltage at 0.05C; discharge to 2.8V with constant current at 0.3C, continuously cycle for 200 / 500 / 1000 cycles. 5) Capacity retention rate calculation formula: Capacity retention rate (%) = Discharge capacity in the nth cycle / Initial discharge capacity × 100%.
[0073] 2. Thermal runaway trigger temperature test: The accelerated calorimeter (ARC) test was conducted using the following steps: 1) After 50 cycles, fully charge the battery to 4.3V and place it in the ARC insulation chamber.
[0074] 2) Heating-Wait-Search (HWS) mode is adopted: temperature increment: 5℃, waiting time: 15min, self-heating threshold: 0.02℃ / min. 3) The instrument automatically monitors the changes in battery temperature, pressure, and temperature rise rate over time.
[0075] 4) Record key parameters: T1: self-exothermic onset temperature; T2: thermal runaway trigger temperature (point where the temperature rise rate spikes sharply); maximum thermal runaway temperature, maximum temperature rise rate, and gas production pressure.
[0076] Test Results The test results of the batteries assembled in the examples and comparative examples are shown in the table below:
[0077] The results in the table above show that adding an appropriate proportion of reactive oxygen species inhibitors, i.e., free radical quenchers, to the ceramic layer can effectively improve the thermal stability and needle penetration stability of solid-state batteries. In Comparative Example 1, no ceramic layer was set on the surface of the positive electrode active material layer, resulting in a risk of thermal runaway and a low thermal runaway trigger temperature. At the same time, the initial discharge capacity was also lower than that of the example. In Comparative Example 2, the ceramic layer did not contain free radical quenchers, resulting in a risk of thermal runaway and a low thermal runaway trigger temperature. In Comparative Example 3, the content of free radical quenchers in the ceramic layer was too low, resulting in no risk of thermal runaway, but the thermal runaway trigger temperature was 200°C, and the initial discharge capacity was also low. In Comparative Example 4, the content of free radical quenchers in the ceramic layer was too high, resulting in a risk of thermal runaway.
[0078] As can be seen from the above, this application provides a battery positive electrode sheet, which includes a positive electrode current collector, a positive electrode active material layer, and a ceramic layer stacked sequentially. The ceramic layer comprises the following components by mass percentage: 60wt%-70wt% ceramic powder, 3wt%-8wt% free radical quencher, 25wt%-30wt% lithium salt, and 1wt%-3wt% film-forming aid. The ceramic powder includes one or more of LiAlO2, LiAl5O8, LLZO, Li3BO3, Li2ZrO3, LiNbO3, Al2O3, MgO, and ZrO2. The free radical quencher includes one or more of trimethylboronic acid ester, tri(fluoromethyl)boronic acid ester, 2,4,6-tri(trifluoromethyl)phenylboronic acid ester, TEMPO, OH-TEMPO, TEMPO-OSO3Li, antioxidant 1010, antioxidant 1076, and N,N'-diphenyl-p-phenylenediamine. The lithium salt includes one or more of LiFSI, LiTFSI, LiPF6, LiDFOB, LiBOB, and LiBF4. The film-forming aid includes one or more of PEG, PEO, PPG, PVA, PVP, PVDF, and PVDF-HFP. The above-described ceramic layer design has the following advantages: Improved interface stability: The ceramic layer can improve the scavenging rate of oxidative free radicals, reduce the amount of sulfide electrolyte oxidation and decomposition, and maintain the capacity retention rate of the battery at ≥88% after 500 cycles; Safety performance optimization: The thermal runaway trigger temperature has been increased from 177℃ to over 195℃, the maximum thermal runaway temperature rise has been reduced by 30%, and no fire or explosion occurred during the needle penetration test (existing technology is prone to thermal runaway). Reduced interface impedance: The ion-conducting design of the ceramic layer reduces the interface impedance between the positive electrode and the electrolyte by 40%-55%, improving the battery rate performance and maintaining ≥95% of the 1C discharge capacity. Excellent compatibility: The ceramic layer is fully compatible with existing ternary cathode materials and sulfide electrolyte systems, requiring no modification to production equipment and reducing the increase in mass production costs.
[0079] The above are merely preferred embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A battery positive electrode sheet, characterized in that, The battery positive electrode sheet includes a positive current collector, a positive active material layer and a ceramic layer stacked in sequence, wherein the ceramic layer contains ceramic powder and a free radical quencher.
2. The battery positive electrode sheet according to claim 1, characterized in that, The proportion of free radical quencher in the ceramic layer is 3wt%-8wt%; Preferably, the free radical quencher includes one or more of trimethylboronic acid ester, tri(fluoromethyl)boronic acid ester, 2,4,6-tri(trifluoromethyl)phenylboronic acid ester, TEMPO, OH-TEMPO, TEMPO-OSO3Li, antioxidant 1010, antioxidant 1076, and N,N'-diphenyl-p-phenylenediamine.
3. The positive electrode of the battery according to claim 1, characterized in that, The ceramic powder content in the ceramic layer is 60wt%-70wt%; Preferably, the ceramic powder includes one or more of LiAlO2, LiAl5O8, LLZO, Li3BO3, Li2ZrO3, LiNbO3, Al2O3, MgO, and ZrO2.
4. The positive electrode of the battery according to claim 1, characterized in that, The ceramic layer also contains lithium salt and film-forming aids; Preferably, the lithium salt content in the ceramic layer is 25wt%-30wt%, and the film-forming aid content is 1wt%-3wt%. Preferably, the lithium salt includes one or more of LiFSI, LiTFSI, LiPF6, LiDFOB, LiBOB, and LiBF4, and the film-forming aid includes one or more of PEG, PEO, PPG, PVA, PVP, PVDF, and PVDF-HFP.
5. The positive electrode sheet of the battery according to any one of claims 1-4, characterized in that, The ceramic layer comprises the following components by weight percentage: 60wt%-70wt% ceramic powder, 3wt%-8wt% free radical quencher, 25wt%-30wt% lithium salt, and 1wt%-3wt% film-forming aid; Preferably, the thickness of the ceramic layer is 1μm-15μm.
6. A method for preparing a battery positive electrode sheet according to any one of claims 1-5, characterized in that, include: The positive electrode active material layer and the ceramic layer are sequentially coated on the surface of the positive electrode current collector to obtain the battery positive electrode sheet.
7. The preparation method according to claim 6, characterized in that, The method of coating the ceramic layer includes: preparing a slurry from ceramic powder, free radical quencher, lithium salt, and film-forming aid, coating it onto the surface of the positive electrode active material layer, and drying it to obtain a battery positive electrode sheet; Preferably, ceramic powder, free radical quencher, lithium salt, film-forming aid and organic solvent are mixed and ball-milled for 1h-24h to form a uniform slurry, which is then coated on the surface of the positive electrode active material layer and vacuum dried at 80℃-120℃ for 1h-8h to form a ceramic layer with a thickness of 1μm-15μm. Preferably, the organic solvent includes anisole.
8. A solid-state battery, characterized in that, The solid-state battery includes a positive electrode, a negative electrode, and a solid electrolyte sheet located between the positive electrode and the negative electrode. The positive electrode is prepared by the method described in any one of claims 1-5 and / or any one of claims 6-7.
9. The solid-state battery according to claim 8, characterized in that, The electrolyte in the solid electrolyte sheet includes a sulfide electrolyte.
10. An electrical appliance, characterized in that, The electrical device includes the solid-state battery as described in claim 8 or 9.